2014
DOI: 10.3892/mmr.2014.3077
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of polo-like kinase 2 increases cell proliferation and decreases apoptosis in SGC-7901 gastric cancer cells

Abstract: Abstract. Polo-like kinase 2 (PLK2) is a serine/threonine protein kinase, which has vital roles during mitosis and the centrosome cycle. In acute myeloblastic leukemia and hepatocarcinogenesis, PLK2 acts as a tumor suppressor; however, the function of PLK2 in gastric cancer remains to be elucidated. In the present study, PLK2 was overexpressed in gastric cancer tissues and three types of gastric cancer cells, SGC-7901, MKN-45 and BGC-823. Transfection of SGC-7901 gastric cancer cells with small interfering (si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
(36 reference statements)
3
10
0
Order By: Relevance
“…The above studies demonstrate the tumor‐promoting role of PLK2. However, many other studies have indicated that it is a tumor suppressor . In agreement with previous studies, PLK2 inhibition promoted cell cycle progression and cell proliferation in normal culture Saos2 cells, indicating its role as a suppressor.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The above studies demonstrate the tumor‐promoting role of PLK2. However, many other studies have indicated that it is a tumor suppressor . In agreement with previous studies, PLK2 inhibition promoted cell cycle progression and cell proliferation in normal culture Saos2 cells, indicating its role as a suppressor.…”
Section: Discussionsupporting
confidence: 90%
“…it is a tumor suppressor [66,67]. In agreement with previous studies, PLK2 inhibition promoted cell cycle progression and cell proliferation in normal culture Saos2 cells, indicating its role as a suppressor.…”
Section: (A) (B)supporting
confidence: 92%
“…Methylated PLK2 was shown to be predictive of OS, with cases with a PFS of less than 12 months showing the highest levels compared with the remainder of the cohort. Our data showing the relationship between PLK2 drug induced apoptosis are supported by Liu et al [18] who showed that PLK2 silenced gastric carcinoma cells were resistant to apoptosis, showing reduced levels of caspase-3 protein. The authors also provided evidence for PLK2 as a tumour suppressor, since gastric carcinoma cells showed a significantly enhanced growth rate when transfected with PLK2 SiRNA.…”
Section: Discussionsupporting
confidence: 86%
“…This accounts for glioblastoma [ 168 ], hepatocellular carcinoma [ 169 ], acute myeloid leukemia [ 170 ], and for B-cell malignancies [ 171 ] where PLK2 is epigenetically silenced, as well as for cervical cancer where PLK2 exhibits anti-proliferative and apoptosis-promoting effects [ 172 ]. This accounts for gastric cancer, too, according to siRNA-mediated PLK2 knockdown [ 173 ]. In breast cancer, reduced PLK2 expression is linked to adverse prognosis [ 174 ].…”
Section: Plks and Tumor Developmentmentioning
confidence: 99%